AN INVESTIGATION AUTHORITY OF CRIMINAL ACT ON CORRUPTION IN CRIMINAL JUSTICE SYSTEM IN INDONESIA - Sukmareni Sukmareni (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Investigation of corruption, requires special provisions nonscheduled general criminal law. Investigation of corruption that were previously carried out by the police or the prosecutor's office, it turns out in practice raises legal issues at the level of implementation. Therefore, the establishment of the Corruption Eradication Commission (KPK) is going forward in the study referred to by the Commission through Act No. 30 of 2002 as an independent agency is expected to help accelerate the eradication of corruption in Indonesia. Establishment of the Commission resulted in differences in investigation and prosecution of corruption, has been authorized to investigate the criminal acts of corruption only at the police investigators and prosecutors, now compounded one another institution which has the authority investigation in Indonesia, namely the Commission. Investigator Police authority in the investigation of corruption offenses based on Law No. 8 of 1981 on the Law of Criminal Procedure Code and Law No. 2 of 2002 on the Police, while the authority of the Attorney Investigator by the Criminal Procedure Code and the Law No.16 of 2004 on the Prosecutor and Law No. 28 of 1999 on Corruption, Collusion and Nepotism and Act 8 of 2010 on Money Laundering. KPK investigators and the authority under the Act No. 30 of 2002 on Corruption Eradication Commission . Giving investigative authority at 3 above institutions (police investigation, prosecutor investigators and the KPK investigators) turned in its implementation raises several issues, among others, 1) differences in interpretation of the respective authorities of investigating corruption, 2) the willingness of the parties to protect fellow colleagues who indicated to corruption, 3) lack of coordination among the three agencies authorized to conduct the investigation corruption itself. This could hamper the acceleration of the eradication of corruption in Indonesia. Therefore it is necessary to do further research to find a model investigation of corruption are ideal to be applied in the Indonesian criminal justice system, which is expected to be able to help accelerate the eradication of corruption itself Keywords : Authorities, Investigation of Corruption, the Criminal Justice System Indonesia